2016
DOI: 10.1080/14739879.2016.1217170
|View full text |Cite
|
Sign up to set email alerts
|

How can educators support general practice (GP) trainees to develop resilience to prevent burnout?

Abstract: This research demonstrates that high levels of burnout are experienced in GP trainees as early as the first year of training. Early identification of burnout amongst trainees is essential by GP educators to help protect the future GP workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…There are increasing evidences supporting the significant function of turnover intention on nurse burnout (Havaei et al., ; Sales, Macdonald, Scallan, & Crane, ). Our study provides additional evidence.…”
Section: Discussionmentioning
confidence: 99%
“…There are increasing evidences supporting the significant function of turnover intention on nurse burnout (Havaei et al., ; Sales, Macdonald, Scallan, & Crane, ). Our study provides additional evidence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, burnout may be accelerated in clinics that have too few GP resources available to serve the patient base (An et al, 2009;Chen et al, 2013;Oskrochi et al, 2016;Nanda et al, 2017;Picquendar et al, 2018). A previous Danish study among 216 GPs found the seven-year incidence of burnout was 13% and, among 48 GP trainees in the UK, Sales et al demonstrated that signs of burnout develop from the beginning of a GP's career (Pedersen et al, 2013;Sales et al, 2016). While patients may prefer the service, accessibility, and facilities of single-handed practices, GPs in single-handed practices may experience higher levels of job stress (McKinnon et al, 1999;McDonald et al, 2009;van den Hombergh et al, 2009).…”
Section: Discussion Of Study Findingsmentioning
confidence: 99%
“…Personal resilience can be defined as an ‘emotional competence’ which involves the cognitive processes of self-efficacy, planning, self-control, commitment, and perseverance [ 10 12 ]. It has been discussed as an essential skill for doctors which can help mitigate against burnout [ 10 , 13 , 14 ] and empathic erosion [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%